2023
DOI: 10.5551/jat.ed227
|View full text |Cite
|
Sign up to set email alerts
|

MAFLD and ASCVD: Plasma Heparin Cofactor II Activity as an Anti-liver Fibrosis Biomarker

Abstract: Michio ShimabukuroHosono K, Saito S and Nakajima A: Risk of cardiovascular disease in patients with fatty liver disease as defined from the metabolic dysfunction associated fatty liver disease or nonalcoholic fatty liver disease point of view: a retrospective nationwide claims database study in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…35 MAFLD disrupts the natural equilibrium between energy intake and expenditure in the body, causing fat to accumulate in the liver and vascular walls and ultimately leading to fatty liver, liver insulin resistance, and atherosclerotic cardiovascular disease (ASCVD). [36][37][38][39][40][41][42] When hepatic steatosis modifies hepatocytokine secretion, it creates a complementary reciprocal condition that affects fatty acid metabolism and insulin resistance in various tissues, including skeletal muscle, cardiovascular smooth muscle, adipose tissue, and the liver. 43 Previous studies have shown that NAFLD is independently associated with chronic macrovascular and microvascular complications, especially with PAD in T2DM 44,45 and its mechanism may involve dyslipidemia, increased insulin resistance, modifications in hemostaticfibrinolytic factors, elevated proinflammatory cytokines, and dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…35 MAFLD disrupts the natural equilibrium between energy intake and expenditure in the body, causing fat to accumulate in the liver and vascular walls and ultimately leading to fatty liver, liver insulin resistance, and atherosclerotic cardiovascular disease (ASCVD). [36][37][38][39][40][41][42] When hepatic steatosis modifies hepatocytokine secretion, it creates a complementary reciprocal condition that affects fatty acid metabolism and insulin resistance in various tissues, including skeletal muscle, cardiovascular smooth muscle, adipose tissue, and the liver. 43 Previous studies have shown that NAFLD is independently associated with chronic macrovascular and microvascular complications, especially with PAD in T2DM 44,45 and its mechanism may involve dyslipidemia, increased insulin resistance, modifications in hemostaticfibrinolytic factors, elevated proinflammatory cytokines, and dysbiosis.…”
Section: Discussionmentioning
confidence: 99%